POETRY TRANSLATION ACCEPTABILITY ON THE TRIALS OF APOLLO: THE HIDDEN ORACLE NOVEL - Sukmajati, Bintang; Angelina, Patricia (International Journal of Humanity Studies (IJHS), 2019)
This study aims to find out the extent of the acceptability of the poetry translation in the novel. One research question is formulated: To what extent is the poetry translations in The Trials of Apollo: The Hidden Oracle acceptable based on Larsons criteria of an acceptable translation. Qualitative research by using the text analysis was conducted. The data of this research were taken from both the English and Indonesian version of The Trials of Apollo: The Hidden Oracle novel. In order to answer the research question, the researchers compared the translation between the English and Indonesian poetry using the theory of acceptability by Larson. The results show that there are 36 poetry translations which are categorized as acceptable and three poetry translation which are unacceptable. The 36 poetry translations incorporate at least two out of the three poetry translations acceptability criteria, while the three poetry only fulfil one poetry translation acceptability criterion.DOI: 10.24071/ijhs.2019.030107